Implikasi Hukum Praktik Konstruksi Terhadap Perjanjian Pemborongan Bangunan - Yusri Ikromi (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2024)
The implications of subcontracting agreements in Indonesia's construction practice hold significant importance in ensuring project efficiency. This research highlights crucial factors to consider, including compliance with the law, efficient dispute resolution, workers' rights protection, and risk management. Adhering to construction and civil code regulations, alongside considering alternative dispute resolution, mitigates legal risks. Ensuring workers' rights protection and implementing robust risk management contribute to project success. By understanding and applying these implications, the practice of subcontracting agreements can achieve a harmonious and productive balance in construction project execution in Indonesia. Emphasizing these aspects will result in smoother operations, minimized conflicts, and improved overall project outcomes, ultimately leading to successful construction project completion in Indonesia. The consideration of these factors in the construction industry can positively impact project outcomes and lead to more effective and successful construction projects. This research highlights the significant role of contracting agreements in construction practices in Indonesia in ensuring project efficiency. It focuses on crucial factors that need attention, including compliance with the law, efficient dispute resolution, protection of workers' rights, and risk management. Adhering to construction laws and the Civil Code (KUHPerdata), as well as considering alternative dispute resolution, helps mitigate legal risks. Protecting workers' rights and implementing good risk management contribute to project success. By understanding and applying these implications, contracting practices can achieve a harmonious and productive balance in implementing construction projects in Indonesia. Emphasizing these aspects will result in smoother operations, reduced conflicts, and overall project improvement, ultimately leading to successful construction project completion in Indonesia. Consideration of these factors in the construction industry can have a positive impact on project outcomes, resulting in more effective and successful construction projects.